Retrospective Study 2019–2021 of Antimicrobial Resistance in Escherichia coli, Klebsiella pneumoniae, and Proteus mirabilis in Mexicali, Mexico - Dolores A. Márquez-Salazar; Ricardo Delgadillo-Valles; Gerson N. Hernández-Acevedo; Edwin Barrios-Villa; Raquel Muñiz-Salazar; Gilberto López-Valencia; Rafael Martínez-Miranda; Jonathan Arauz-Cabrera (Microbiology Research)
Community-acquired infections caused by Enterobacterales are a growing public health concern, particularly in border regions where patient mobility may influence resistance patterns. Antimicrobial resistance (AMR) surveillance is critical for establishing local treatment guidelines. The aim of this study was to investigate AMR rates in clinical isolates of Escherichia coli, Klebsiella pneumoniae, and Proteus mirabilis obtained from community-acquired infections in Mexicali between 2019 and 2021. A retrospective study was conducted, analyzing 2871 Enterobacterales isolates (E. coli, K. pneumoniae, P. mirabilis). Species identification and antimicrobial susceptibility testing were performed using MALDI-TOF and VITEK 2 systems, interpreted according to CLSI and EUCAST breakpoints. ESBL production was detected in 37.6% of E. coli, 27.7% of K. pneumoniae, and none of the P. mirabilis isolates. Among ESBL producers, ciprofloxacin resistance reached 90.4% in E. coli and 81.0% in K. pneumoniae, indicating a significant level of co-resistance. Carbapenem-resistant K. pneumoniae (n = 13) and one E. coli isolate were also identified, all from community-acquired infections. Resistance patterns varied by infection site, with UTIs accounting for the majority of isolates. The high rates of ESBLs and co-resistance to ciprofloxacin among Enterobacterales highlight the urgent need for targeted AMR surveillance and site-specific empirical treatment strategies.